Whose Heritage? Challenging Race and Identity in Stuart Hall's Post-nation Britain - Ashley, Susan L.T; Stone, Degna (Taylor & Francis, 2023)
This edited collection challenges and re-imagines what is 'heritage' in Britain as a globalised, vernacular, cosmopolitan 'post-nation'. It takes its inspiration from the foundational work of public intellectual Stuart Hall (1932-2014). Hall was instrumental in calling out embedded elitist conceptions of 'The Heritage' of Britain. The book's authors challenge us to reconsider what is valued about Britain's past, its culture and its citizens. Populist discourses around the world, including Brexit and 'culture war' declarations in the UK, demonstrate how heritage and ideas of the past are mobilised in racist politics. The multidisciplinary chapters of this book offer critical inspections of these politics, and dig deeply into the problems of theory, policy and practice in today's academia, society and heritage sector. The volume challenges the lack of action since Hall rebuked 'The Heritage' twenty years ago. The authors featured here are predominantly Black Britons, academics and practitioners engaged in culture and heritage, spurred by the killing of George Floyd and the rise of the Black Lives Matter movement to contest racist practices and structures that support them. The primary audience will be academics, but it will also attract culture sector practitioners and heritage institutions. However, the book is particularly aimed at scholars and community members who identify as Black, who are centrally concerned with questions of identity and race in British society. Its Open Access status will facilitate access to the book by all groups in society.